(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
Integrated Projects is a multidisciplial educational activity that integrates different disciplines such as math, science and engineering into a single project. These projects allow students to apply their knowledge and skills to solving real problems, develop critical thinking and problem-solving abilities.